Computer Literacy for College-Level Philosophy Students at National Taiwan University - Lin, Yuan-Lih. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This paper analyzes a proposal for integrating computer literacy into undergraduate level philosophy study at the National Taiwan University and suggests definitions and curriculum formats. The paper proposes a new definition of language and a multi-dimensional definition of computer literacy. These are then applied to the undergraduate education of the philosophy department. This application involves recommendations for a revision of the current curriculum, analysis of the definition of computer literacy, scrutiny of the changing role of teachers, students, and the philosophy department, discussion of teachers' and students' backgrounds, and analysis of the philosophical foundations and social implications of using computers in the curriculum and instruction of the Department. The paper's conclusion, based on Ludwig Wittgenstein's theory of language as "language games," argues that, as language games are for communication, computer literacy in the philosophy department is a communication between philosophy, all subject matters about human beings, and the computer. In addition, the end or goal of the game is to make college philosophy students intellectual and wise in a new age, and that college philosophy students are computer-literate in the communication contest among philosophy, subject matters about human beings, and the computer. (JB)
ERIC Note: Master's Thesis, University of Wisconsin, Madison.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Chinese Culture; College Faculty; College Instruction; College Students; Computer Literacy; Computer Uses in Education; Curriculum Development; Foreign Countries; Higher Education; Philosophy; Student Role; Teacher Role; Undergraduate Study; National Taiwan University; Wittgenstein (Ludwig); Dissertations/Theses, Masters Theses; Opinion Papers